Estudio Del Cambio Global En Los Regímenes Hídricos De Los Ríos Guayas, Esmeraldas, Napo, Santiago (Pacífico), Jubones Y Mira - Dos Santos Duque Joselyn Briguitte (2022)
Tesis previa obtención del título de Licenciado/a en Gestión Ambiental